Face Attractiveness versus Artistic Beauty in Art Portraits: A Behavioral Study - Schulz, Katharina; Hayn-Leichsenring, Gregor U. (Frontiers in Psychology, 2017)
Abstract From art portraits, the observer may derive at least two different hedonic values: The attractive-ness of the depicted person and the artistic beauty of the image that relates to the way of presentation. We argue that attractiveness is a property that is predominantly driven by percep-tual processes, while the perception of artistic beauty is based predominantly on cognitive pro-cessing. To test this hypothesis, we conducted two behavioral experiments. In a gist study (Experiment 1), we showed that ratings on attractiveness were higher after short-term presentation (50ms) than after long-term presentation (3000ms), while the opposite pattern was found for artistic beauty. In an experiment on perceptual contrast (Experiment 2), we showed that the perceptual contrast effect was stronger for attractiveness than for artistic beauty. These results are compatible with our hypothesis that appreciation of artistic beauty is cognitively modulated at least in part, while processing of attractiveness is predominantly driven perceptually. This dichotomy between cognitive and perceptual processing of different kinds of beauty suggests the participation of different neuronal mechanisms.